THE ROLE OF EMBRIOGENETIC FAKTORS IN THE TEROTEGENESIS OF ANORECTAL MALFORMATION - Yuldashеv Muzaffar; Toshboеv Shеrzod; Mirzakarimov , Baxrom (Medical science of Uzbekistan, 2022)
Anorectal malformations (ARP) are congenital malformations that are common in pediatric surgery. Although surgi-cal procedures correct anatomical abnormalities, postoperative bowel function is not always satisfactory. The etiology of ARM remains unclear. In this review, summarize the current understanding of embryological and genetic factors contrib-uting to the pathogenesis of ARM, based on published animal models, human genetic studies, and epidemiological studies. Better understanding of these factors could help manage ARM better.